Geographical variability and parasitism on body size, reproduction and shell characteristics of the keyhole limpet Fissurella crassa (Mollusca: Vetigastropoda) - García-Huidobro, M. Roberto; Aldana, Marcela; Varas, Oscar; Pulgar, José; García-Herrera, Claudio; Abarca-Ortega, Aldo; Grenier, Christian; Rodríguez-Navarro, Alejandro B.; Lagos, Nelson A. (Marine environmental research, 2020)
Environmental variation may alter biological interactions and their ecological consequences. For instance, in marine ecosystems hosts and parasites are subject to environmental variability across latitudinal gradients, and their co-evolutionary dynamics may be the result of the interplay with local physical-chemical variables in seawater. Thus, assessing the environmental conditions required for a host in order to improve their survival is essential to understand the host-parasite interaction and dynamics. In this study, we evaluated the impact of parasitism by Proctoeces humboldti on the body size and reproduction of the intertidal keyhole limpet Fissurella crassa collected from three populations spanning ca. 1500 km along the latitudinal gradient of the Chilean coast. In addition, for the first time, we explore whether the effect of parasitism can be extended to changes in the organic composition and mechanical properties of the host shell. Our results show that parasitism prevalence and intensity, and body size of F. crassa increased in central Chile (ca. 33°S). Unlike body size, which was greater in parasitized limpets than in non-parasitized limpets at the three study sites, reproductive performance followed this trend only in central Chile populations, with no differences between parasitized and non-parasitized limpets collected in the northern Chilean (ca. 23°S), and lower in parasitized than non-parasitized individuals from the south-central Chile (ca. 37°S). The organic composition of F. crassa shells showed significant differences between parasite conditions (e.g. polysaccharides and water decreased in parasitized limpets) and across sites (e.g. proteins levels increase in shell of parasitized limpets from central Chile, but decreased at south-central Chile). However, variability in shell mechanical properties (e.g. toughness and elastic module) do not showed significant differences across sites and parasitism condition. These results suggest the interplay of both parasitism and environmental fluctuations upon the reproductive performance and morphology of the host. In addition, our result highlight that the host may also trade-offs reproduction, growth and shell organic composition to maintain the shell functionality (e.g. protection for mechanical forces and durophagous predators). •It is explored whether parasitism can change the organic and mechanical composition of the shell of its host.•The organic composition of shell showed differences between parasitism condition along Chile.•The host may also trade-offs reproduction, growth and shell organic composition for to maintain the shell functionality.